Differential Metabolic Impact of Natural Food-Grade Emulsifiers Rich in Alpha-Linolenic Acid. (29th May 2020) - Robert, Chloe; Buisson, Charline; Couëdelo, Leslie; Meugnier, Emmanuelle; Knibbe, Carole; Loizon, Emmanuelle; Fonseca, Laurence; Laugerette, Fabienne; Vaysse, Carole; Michalski, Marie-Caroline
Abstract: Objectives: Dietary synthetic emulsifiers have recently been shown to promote metabolic syndrome and considerably alter gut microbiota. Conversely, natural emulsifiers such as milk polar lipids (PL) are associated with beneficial metabolic effects. The effects of plant PL remain, however, poorly described. Our objective was to evaluate, using two complimentary rodent models, the impact of nutritional doses of lecithin (≤10%) of vegetal sources alternative to soy on gut microbiota, postprandial lipid metabolism, and the bioavailability of an essential plant lipid, alpha-linolenic acid (ALA). Methods: For 5 days, male Swiss mice ( n = 60) were fed normolipidic diets (identical ALA content) containing 0, 1, 3 or 10% rapeseed lecithin (RL) or 10% soy lecithin. Following an overnight fast, the mice were force-fed the same oil mix and euthanised after 90 min. As a mechanistic study, male Wistar rats ( n = 30) with mesenteric duct cannulation were fed 5 oil mixtures containing 0 to 20% RL. Lymph fractions were collected up to 6 h post-gavage. Plasma and lymph lipid composition was determined using GC-FID, chylomicron (CM) size using light-scattering spectroscopy, and intestinal gene expression and faecal microbiota composition by RT-qPCR. Results: In mice, the consumption of lecithin significantly increased levels of faecal Clostridium leptum ( P < 0.001), regardless of lecithin origin or dose. The partial replacement of oil with lecithin did not significantly alter plasma total lipids nor the expression of genes of intestinal lipid absorption. The percentage of ALA in plasma triglycerides was significantly higher in the 10% RL group compared to other groups ( P < 0.05). In rats, RL significantly and dose-dependently increased the rate of appearance ( P < 0.01) and concentration of ALA in lymph ( P < 0.01). 20% RL additionally increased CM size and expression of genes of CM secretion (Mttp, Sar1b; P < 0.05). Conclusions: Our results reveal that, whereas both rapeseed and soy lecithin improved gut microbiota composition by increasing the anti-inflammatory Clostridium leptum bacterial group, only rapeseed lecithin enhanced ALA bioavailability. This study illustrates the importance of considering the use of natural emulsifiers, especially rapeseed lecithin, as plant-based food ingredients with potential health benefits. Funding Sources: ANRT and UMT ACTIA BALI.